"Lesbian"/female same-sex sexualities in Africa. Issue 2 (3rd April 2017) - Currier, Ashley; Migraine-George, Thérèse
ABSTRACT: Understandings of African lesbian sexualities have been affected by silence, repression, and uncertainty. The subject of lesbian experiences and sexualities in Africa constitutes an opportunity for feminist scholars to address the transnational politics of knowledge production about African lesbians' lives and the contours of lesbian art, activism, and relationships in African nations. This article contextualizes the state of research on African lesbian sexualities and introduces the special issue.